Knowledge, perceptions and use of generic drugs: a cross sectional study - Lira,Claudio Andre Barbosa de (2014)
Objective To assess the level of knowledge, perceptions and usage profile for generic drugs among laypersons. Methods A cross-sectional study was conducted with 278 volunteers (180 women and 98 men, aged 37.1±15.8 years). A questionnaire was drawn up with questions on their use, perceptions and knowledge of generic drugs. Results Most respondents (99.6%) knew that generic drugs exist, but only 48.6% were able to define them correctly, while 78.8% of the respondents had some information about generics. This information was obtained mainly through television (49.3%). In terms of generic drug characteristics, 79.1% stated that they were confident about their efficacy, 74.8% believed that generic drugs have the same effect as branded medications, 88.8% said that generics were priced lower than branded medications, and 80.2% stated that they bought generic drugs because of price. With regard to drugs prescribed by medical practitioners, 17.6% of the participants said that their doctors never prescribed generics and only 7.5% confirmed that their doctors always prescribed generics. Conclusion For the lay public, the sample in this study has sufficient knowledge of generic drugs in terms of definition, efficacy and cost. Consequently, the volunteers interviewed are very likely to use generics. Furthermore, the results of this study indicate that programs should be implemented in order to boost generic drug prescriptions by medical practitioners.